Complaints against rural doctors : the impacts on the quality of rural health care services and on rural communities : a thesis presented in partial fulfilment of the requirements for the degree of Master in Management at Massey University, Palmerston North, New Zealand - Henderson, Robert Frank (Massey University, 2003)
Investigations of health care complaints are assumed to improve the standards of health care but this belief has not been tested. Using a multiple case study in sixteen remote rural areas, this study examined the effects of formal investigations of complaints on the quality of health care services and the effects on the community. Data for the study were obtained from in-depth interviews, documents and observations. Rural doctors, who struggled to cope with a heavy workload, isolation and many other difficulties, found the accusations of incompetence and the prolonged disciplinary process very threatening. The disciplinary process was more damaging than the findings. The effects of the process were: a few doctors developed a post-traumatic stress like disorder - being unable to cope with threatening situations, some doctors left and were difficult to replace, while others lost their enthusiasm for their work and adopted defensive medical practices. These defensive practices included setting up barriers to access, working more slowly, ordering more investigations and referring more people to secondary care. Other local health workers regarded the disciplinary process as a threat to them also and they adopted similar negative attitudes, as did many distant doctors who heard about the investigation. The fragile local health systems were damaged by the adversarial disciplinary process and became less efficient and less user friendly. Rural communities became involved in the adversarial process and it appeared some complainants were subjected to community pressure. Complainants also had difficulty accessing further health care services and they appeared worse off for having complained. There is an urgent need to develop better ways of dealing with complaints so that the complaint process may: find answers to the problems of health care delivery rather than damaging health care services, serve complainants better, and are fairer on health professionals. Many of the answers to a better system of complaint management are to be found in studies on: quality control in organisations, error control, safe systems in aviation and similar studies.
Keywords: Physicians (General practice); Rural health services; Rural medicine; Complaints; New Zealand; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management